Investigating the properties and antibacterial, antioxidant, and cytotoxicity activity of postbiotics derived from Lacticaseibacillus casei on various gastrointestinal pathogens in vitro and in food models - Asadi, Zahra; Abbasi, Amin; Ghaemi, Ali; Montazeri, Effat Abbasi; Akrami, Sousan (German Medical Science GMS Publishing House, 2024)
Background: Postbiotics comprise soluble compounds freed from the structure of destroyed bacteria or created by living bacteria. Such byproducts provide the host with enhanced biological function as well as specific physiological consequences. This research aims to examine the characteristics and possible health advantages of -derived postbiotics. Methods: The antibacterial effects of postbiotics derived from were examined in vitro against various infectious gastrointestinal agents, as well as pasteurized milk and minced beef. Postbiotic activity potential was evaluated using disc-diffusion agar, minimum inhibitory concentration, minimum bactericidal concentration, and well-diffusion agar methods. Postbiotics were tested for antioxidant activity against zinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) free radicals. Additionally, the total phenolic and flavonoid content of the postbiotics was determined. The colorimetric MTT was used to investigate the potential cytotoxicity of postbiotics. The chemical makeup of the postbiotics was also determined using gas chromatography/mass spectrometry. Results: The antibacterial capacity was mostly related to pyrrolo[1,2-a] pyrazine-1,4-dione, benzoic acid, and laurostearic acid. Gram-positive microbes were more influenced by microbial byproducts in vitro than Gram-negative bacteria (P<0.05). The minimum effective concentrations of postbiotics were found to be much greater in ground beef and milk in the -inoculated model than with other bacteria (P<0.05). Postbiotics also show high antioxidant activity. Postbiotics generated from had the greatest concentrations of phenolic (99.46 mg GAE/g) and flavonoid (17.46 mg QE/g) constituents. Postbiotics had no influence on the viability of human foreskin fibroblasts at any dose. Conclusion: spp. postbiotics, particularly , were recommended for use as antioxidants, antimicrobials, and preservatives in both the food and pharmaceuticals sector for their beneficial effects and biological properties.